OPTIMASI PEMANFAATAN WISATA BAHARI BAGI PENGELOLAAN PULAU-PULAU KECIL BERBASIS MITIGASI (Kasus Kawasan Gili Indah Kabupaten Lombok Utara Propinsi Nusa Tenggara Barat) - Amir, Sadikin; Yulianda, Fredinan; G.Bengen, Dietriech; Boer, Mennofatria (FAPETKAN UNTAD, 2011)
The increasing of tourism activities magnified by uncontrolled land use patterns have caused coastal ecosystem degradation in Gili Indah. A research on evaluation of land use patterns and optimization of coastal tourism based on a mitigation approach has been done in the area. Research results showed that size of area including in a very suitable category for diving activity were 216.79 ha; 190.84 ha for snorkeling activity; and 19.83 ha for beach tourism. Based on carrying capacity analysis the area can support maximum 286 tourists per day or 104.390 tourists annually. Mitigation approach in optimization indicates that the maximum tourist number in the area can only be reached if all aspects of carrying capacity namely ecological, economics, social and institutional aspect are well considered. Key words : Carrying capacity, coastal tourism, mitigation, optimization.